Investigating the effect of chemotherapeutic agents, Doxorubicin and Paclitaxel, in combination with Dodonaea viscosa on breast cancer - Van Eck, Janke (Stellenbosch : Stellenbosch University, 2026)
Thesis (PhD)--Stellenbosch University, 2025.